DEVELOPMENT OF A PROJECT-BASED LEARNING (PJBL) METHOD USING GOOGLE MEET TO IMPROVE STUDENT LEARNING OUTCOMES IN ISLAMIC EDUCATION SUBJECTS AT UPT SDN 064955 MEDAN AMPLAS - Nasution, Ummi Nadrah; Utari, Anggie Sri; Febrian, M Agil; Saifundi, Saifundi; Daulay, Asrul (Universitas Al-Amien Prenduan, 2025)
This research aims to: (1) determine the results of developing the Google Meet-based PjBL model used to improve student learning outcomes in PAI subjects at UPT SDN 064955 Medan Amplas, (2) ascertain the validity, practicality, and effectiveness of the developed Google Meet-based PjBL learning model used to enhance student learning outcomes in PAI subjects at UPT SDN 064955 Medan Amplas. This research is a type of research and development. The development of the PjBL model used is adapted from the ADDIE model, which then consists of 8 stages, namely; (1) needs analysis, (2) initial prototype design, (3) validation, (4) revision, (5) limited trial, (6) revision, (7) extensive trial, (8) final product review. Research results; the development of the PjBL model has stages; (1) problem presentation, (2) planning and determining learning groups, (3) scheduling, (4) observing product creation, (5) assessment, (6) evaluation. Based on the results of expert validation and trials conducted on the developed product, it can be concluded that this assessment product meets very good criteria and has received a very feasible qualification.